Does Metal Ion Complexation Make Radical Clocks Run Fast? - Horn, Anselm; Clark, Timothy (Journal of the American Chemical Society, 2003)
Ab initio molecular orbital and density functional calculations at the CBS-RAD(QCISD,B3-LYP) level for Li + and at B3LYP for Na +, K +, Cu +, and Ag + reveal that the barrier to ring-closure of the 1 -hexen-6-yl ("Δ(5)-hexenyl") radical to the cyclopentylmethyl radical, a so-called radical clock reaction, is decreased very significantly by complexation of the double bond to metal cations. This barrier lowering should occur on complexation with many metal ions, as shown by calculations on all of the monovalent ions listed above. Additional density functional calculations including explicit solvation of the model system complexed to the lithium ion with tetrahydrofuran suggest that the effect found is not limited to the gas phase but may also be significant in experimental radical clock reactions in solution, even for lithium.
UnivIS-Import:2015-03-09:Pub.2003.forsch.sonder.sfb583.doesme